2015
DOI: 10.1128/jcm.01317-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of FilmArray and Quantitative Real-Time Reverse Transcriptase PCR for Detection of Zaire Ebolavirus from Contrived and Clinical Specimens

Abstract: Rapid, reliable, and easy-to-use diagnostic assays for detection of Zaire ebolavirus (ZEBOV) are urgently needed. The goal of this study was to examine the agreement among emergency use authorization (EUA) tests for the detection of ZEBOV nucleic acids, including the BioFire FilmArray BioThreat (BT) panel, the FilmArray BT-E panel, and the NP2 and VP40 quantitative real-time reverse transcriptase (qRT) PCR assays from the Centers for Disease Control and Prevention (CDC). Specimens used in this study included w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…Therefore, the four discrepant BioThreat-E test-positive results discussed above are consistent with the presence of residual low EBOV concentrations in blood, as was also observed in another study (7).…”
supporting
confidence: 72%
“…Therefore, the four discrepant BioThreat-E test-positive results discussed above are consistent with the presence of residual low EBOV concentrations in blood, as was also observed in another study (7).…”
supporting
confidence: 72%
“…The GeneXpert Ebola assay (Cepheid) and FilmArray Ebola test (BioFire) are 2 other platforms providing a fully integrated and automated PCR workflow for EVD testing, but they still require preloading manipulation steps [8,9,19,20]. In addition, we demonstrated that the Idylla™ prototype Ebola virus test can withstand a short exposure up to 40°C (2 days) and humidity of 70% at 30°C and that the cartridge reagents are stable for 4 months at 30°C, while most other PCR tests require a cold chain [18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there is earlier clearance of virus from serum and plasma than from whole blood (27). Testing of whole blood has an important practical and safety advantage since it does not require specimen processing.…”
Section: Discussionmentioning
confidence: 99%